Greening up the City with Native Species: Challenges and Solutions - Amy Hardberger; Danielle Craig; Catherine Simpson; Robert D. Cox; Gad Perry (Diversity)
Urban green spaces provide many benefits, including to human wellbeing, ecosystem services, and urban wildlife. Thus, there are many reasons to green up urban spaces, especially by using native species. Furthermore, urban green spaces are suited to enhancing biodiversity without negatively impacting food or fiber production. Municipalities and private landowners invest substantially in landscaping and its maintenance. However, much of that outlay supports non-native plants that may be less adapted to local conditions such as rainfall patterns and temperature ranges, thus having greater resource requirements, as well as being less supportive of native wildlife and possessing a greater potential of becoming invasive. Here, we explore ways to increase the use of native plant species in urban settings to reduce the need for watering or chemical application, enhance the support of native species, and reduce the risk of invasion to urban and ex-urban habitats. We identify three main impediments: the perception of native species as less aesthetically pleasing, the availability of native plants in the nursery industry, and the willingness of policymakers to take supportive measures. We propose methods to address all three, providing successful examples from a number of US localities and a case study that demonstrates what drivers might exist and what actions remain to be taken.